Good Moments in Gestalt Therapy: A Descriptive Analysis of two Perls Sessions - Boulet, Donald; Soulière, Michelle; Sterner, Irit (Canadian Journal of Counselling and Psychotherapy, 1993)
Two Gestalt therapy sessions conducted by Fritz Perls were analyzed using a category system that was recently developed for identifying in-session client behaviours that are valued by Gestalt therapists. Two hundred and ten client statements were independently rated by four judges. Descriptive analysis of the combined data revealed a common pattern of therapeutic movement. In both sessions, an initial phase dominated by building block good moments (focusing on client awareness, and expressing feeling directly to other) was followed by a phase characterized by combinations of good moments. Sustained bursts of these complex good moments led to the presence of outcome good moments in therapy. Differences between the two sessions were explored with respect to client characteristics, therapeutic alliance, and therapist interventions. The form and content of therapeutic interventions leading to good moments were examined.